(untitled) (Zaporizhzhia Historical Review, 2021)
The article is devoted to the analysis of the publications on the history of industry of the Southern Ukraine in the magazine ìZhurnal ministerstva gosudarstvennukh immushchestvî (The Ministery for State Property Magazine) (1841 ñ 1870). Among the publications the main part constitute the materials on the history of the agricultural industry of the region. The materials contain lot of statistic information.